Water, Sanitation, Hygiene, and Nutrition in Bangladesh : Can Building Toilets Affect Children's Growth? - Mahmud, Iffat; Mbuya, Nkosinathi (Washington, DC: World Bank, 2015)
This report provides a systematic review of the evidence to date, both published and grey literature, on the relationship between water and sanitation and nutrition. We also survey the potential impact of improved water, sanitation, and hygiene (WASH) on undernutrition. This is the first report that undertakes a thorough review and discussion of WASH and nutrition in Bangladesh. The report is meant to serve two purposes. First, it synthesizes the results/evidence evolving on the pathway of WASH and undernutrition for use by practitioners working in the nutrition and water and sanitation sectors to stimulate technical discussions and effective collaboration among stakeholders. Second, this report serves as an advocacy tool, primarily for policy makers, to assist them in formulating a multisectoral approach to tackling the undernutrition problem.